Subject and strategy : (St. Martin’s Press, 1981)
Subject & Strategy helps students write by offering engaging, teachable readings supported by time-tested pedagogy. Its mix of beloved classics and timely current readings provides exceptional models of writing. Its proven advice on writing and reading, innovative classroom exercises, and engaging writing assignments guide students to choose the rhetorical strategy that best suits their subject and then to use that strategy to achieve their writing purpose. Features include annotated student essays in each mode, extensive apparatus supporting every selection, and a “Writers on Writing” chapter that helps students see themselves as writers.